How Client Capabilities, Vendor Configuration, and Location Impact BPO Outcomes. Issue 2 (3rd April 2018) - Whitaker, Jonathan; Kumar, Sanjeev; Krishnan, M. S.
ABSTRACT: Despite the increasing use of onshore and offshore business process outsourcing (BPO), a comprehensive literature review [38] finds that there has been limited empirical research on BPO outcomes. This article responds to the call for research by developing and testing a conceptual model for BPO outcomes using data from 50 firms publicly traded in the U.S., including 38 firms in the Forbes Global 2000. We find that client firm capabilities, vendor configuration, and country location lead to interesting tradeoffs in the BPO quality, cost, and time outcomes. For example, while multi-sourcing offers advantages such as risk mitigation, client firms encounter reduced BPO time benefits when they use multiple vendors. While onshore BPO can lead to an improved quality, higher onshore labor costs result in lower BPO cost savings. And while offshore destinations such as India offer lower labor costs, time zone differences lead to reduced BPO time benefits.